Strategi Komunikasi Massa untuk Mendorong Pertumbuhan Ekonomi Desa Melalui Sektor Pariwisata - Diana Ainun Maf’ula; Ari Kartiko; M. Alfin Fatikh (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
Tourism is a journey supported by the business world, society, and government. Stating that the economy of a nation is experiencing human marginalization. The media is the mass of the masses in tourism. Tourists will feel more comfortable if they communicate easily because there will be no language misunderstandings. Tourism can also foster healthy competitiveness among individuals. For example, people will compete to attract the attention of tourists through creativity created by displaying accommodation that is consistent with local culture, finding new manufacturing techniques, making unique souvenirs, and continuously coming up with innovations so that tourists can stay...and if you come back, you can still choose a hotel, restaurant, or memento. So that the economy in tourist locations can develop and develop well, the tourism industry must be promoted in a planned and integrated manner that improves the welfare and standard of living of the community.